2020
DOI: 10.1101/2020.04.20.20064873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gastrointestinal symptoms as Covid-19 onset in hospitalized Italian patients

Abstract: ObjectiveTo assess the prevalence of gastrointestinal symptoms and their correlation with need of non-invasive ventilatory support, intensive care unit admission and death in hospitalized SARS-CoV-2 patients. DesignSince February 21 th 2020, all individuals referred to our emergency department for suspected SARS-CoV-2 underwent a standardized assessment of body temperature and pulse oximetry, hematological screening, chest X-ray and/or computed tomography (CT), and SARS-CoV-2 assay on nasopharyngeal swab. Medi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The incidence of nausea and/or vomiting and diarrhea from 41 clinical studies 1,2,4,5,16,22–57 : nausea, n = 34; vomiting, n = 39; diarrhea, n = 39. Values for individual studies are shown together with the median and 95% confidence intervals.…”
Section: How Good Is the Epidemiological Data On The Incidence Of Naumentioning
confidence: 99%
“…The incidence of nausea and/or vomiting and diarrhea from 41 clinical studies 1,2,4,5,16,22–57 : nausea, n = 34; vomiting, n = 39; diarrhea, n = 39. Values for individual studies are shown together with the median and 95% confidence intervals.…”
Section: How Good Is the Epidemiological Data On The Incidence Of Naumentioning
confidence: 99%
“…In an Italian study, mean age of the GI symptoms patients was 68.2 ± 14.2 years with 64% male and 35% female. 11 In this study most common GI symptom was anorexia (69%) followed by ageusia (38%), diarrhea (35%), nausea (31%), vomiting (16%) and abdominal pain (14%). A study done in Bangladesh showed that the common GI symptoms were anorexia (44.7%), diarrhea (35%) and nausea.…”
Section: Resultsmentioning
confidence: 53%
“…12 Another study revealed that among GI symptoms, most common are nausea (4.3%), vomiting (3.8%), diarrhea (3.6%) and abdominal pain (1.2%). 11 Three-fifths of patients with GI symptoms in recent study had co-morbidities and most common co-morbidity was hypertension followed by diabetes. Comorbidities were more (69%) among patients with GI symptoms.…”
Section: Resultsmentioning
confidence: 98%
“…which represent about 20% of those infected, with around 5% mortality in this group (10). Cases with anosmia, hyposmia, and ageusia (11); gastrointestinal conditions with diarrhea (12); and painful abdominal lymphadenopathy (13) have also been identified. The diagnosis is made using clinical symptoms, nasal swab reverse transcriptase-polymerase chain reaction (RT-PCR) for SARS-CoV-2 (gold standard for diagnosis in the acute phase), IgG and IgM serology (later stage), and chest computed tomography (especially in patients with respiratory symptoms).…”
mentioning
confidence: 99%